Assessment of the Long-Term Impact of Crude Oil Contamination on Groundwater Trophic State Index (TSI) in Ekpeyeland - Okidhika, Clinton Umebhidhi; Abule, Esther Chinyere; Okwelle, Peace Lawrence (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study investigates the trophic status of groundwater in Ekpeyeland, Rivers State, Nigeria, with focal point on the long-term ecological and public health implications of nutrient loading induced by crude oil contamination. Using Total Phosphorus (TP) as the key nutrient indicator, groundwater samples were systematically collected from strategically selected four locations: Igbu Ehuda (control site), Igbu Ugbobi, Igbu Upata, and Igbu Ubie, representing varying degrees of exposure to artisanal refining and hydrocarbon-based pollution. Sampling was conducted across both dry and wet seasons to capture seasonal variations in nutrient levels and trophic responses. The measured TP concentrations varied remarkably between seasons and sites, with the control site, Igbu Ehuda, displaying the lowest TP levels ranging from 0.045 to 0.055 mg/L. Conversely, higher TP concentrations were observed in impacted communities, specifically Igbu Ubie (0.04 – 0.06 mg/L) and Igbu Ugbobi (0.05 – 0.051 mg/L), with Igbu Upata showing intermediate concentrations (0.04 – 0.05 mg/L). These concentrations were analyzed using Carlson’s modified Trophic State Index (TSI) equation: TSI = 10 × (6 – ln(48/TP) / ln(2), a model primarily designed for surface water but applied here to characterize nutrient enrichment in groundwater systems. The computed TSI values demonstrated significant spatial and seasonal dynamics. Igbu Ubie, the site most adversely impacted by artisanal refining activities, recorded the highest dry season TSI of 42.58, followed by Igbu Ehuda at 41.84, both exceeding the mesotrophic threshold and tending to eutrophic levels. Meanwhile, Igbu Upata, maintained a relatively low TSI values (41.02 during the dry season), indicative of its relatively primal condition. Seasonal analysis showed a general drop in TP concentrations during the wet season, likely due to effect of dilution from rainfall, decline in refining activity, and increased aquifer recharge. However, the persistence of increased TSI values during the wet season in contaminated sites implies ongoing nutrient loading and limited natural attenuation. The elevated TP concentrations and corresponding TSI values in oil-impacted groundwater systems implied significant nutrient enrichment likely emanating from the leaching of refining byproducts, hydrocarbon degradation intermediates, and improperly managed waste pits. These nutrient loads may stimulate microbial activity, alter biogeochemistry of the aquifer, and engender the survival of pathogenic organisms, posing potential health risks to dependent communities. Overall, the study highlights the effectiveness of TSI as a diagnostic and monitoring model in subsurface environments, especially in oil-bearing regions where conventional groundwater assessments often overlook nutrient dynamics. The findings stress the urgent need for integrated groundwater monitoring frameworks, targeted remediation strategies, and stricter regulation of artisanal refining operations to safeguard environmental and public health in the Niger Delta and similar petroleum-producing areas globally.